2012
DOI: 10.1002/oa.2277
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interobserver Error in the Scoring of Entheseal Changes

Abstract: Although the interpretation of entheses has undergone considerable discussion recently, the role of interobserver error, especially in comparative contexts, has been only sporadically addressed. Using standards developed by Hawkey and Merbs, currently the most widely used system, rates of reproducibility were evaluated in two prehistoric North American skeletal series. Eight observers of varying experience levels scored 17 long bone entheses, representing both fibrous and fibrocartilaginous attachment types, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 14 publications
(23 reference statements)
0
45
1
Order By: Relevance
“…It is unlikely that all those researchers who have recorded agricultural populations routinely score lower than those recording hunter-gatherers, but inter-observer error must be considered. The original report (Hawkey and Merbs, 1995) presented low intra-and inter-observer error, but a recent study (Davis et al, 2013) found higher error rates. These are likely to be caused by the difficulty of using photographs to learn a recording method (Davis et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…It is unlikely that all those researchers who have recorded agricultural populations routinely score lower than those recording hunter-gatherers, but inter-observer error must be considered. The original report (Hawkey and Merbs, 1995) presented low intra-and inter-observer error, but a recent study (Davis et al, 2013) found higher error rates. These are likely to be caused by the difficulty of using photographs to learn a recording method (Davis et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Villotte et al (2010) previously scored six primary FC attachments based on their association with skeletal modification in the medical literature. These have been shown to have characteristic remodeling on the entheseal surfaces (Villotte, 2006), with claims of high replicability (cf., Davis et al, 2012). Yet, response to external loadings is complex and poorly understood, and traditional visual scoring methods may not encompass the full range of human variation, which recently three-dimensional modeling is only beginning to show (Zumwalt, 2006:445).…”
Section: Methodsmentioning
confidence: 93%
“…To these we would add the limitations presented in our ability to reliably score only fibrocartilaginous muscle attachments (cf., Davis et al, 2012;Villotte et al, 2010). If we cannot reliably score large fibrous muscles, this places severe limitations on patterns of interpretation.…”
Section: Activity Reconstructions and Limitationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Inter-observer error, in contrast, was higher. This has also been found to be a problem for visual recording methods Davis et al, 2012b). The new 'Coimbra method' for recording entheses reported a low of 65.3% agreement and a high of 78.1% agreement between scorers, all of whom had considerable experience of recording ECs and were involved in developing the method .…”
Section: Discussionmentioning
confidence: 99%